CAN ISLAMIC PHILANTHROPHIC INSTITUTIONS IN INDONESIA ACHIEVE SDGs? An Emipirical Legal Research - Syamsuri, Syamsuri; Jakiyudin, Ahmad Havid; Cahyani, Meitria (Jurisdictie: Jurnal Hukum dan Syariah, 2024)
Islamic philanthropy is part of Sustainable Development Goals (SDGs) as per Article 3 [b] Presidential Regulation No.111 of 2022, highlighting the legal framework (Presidential Regulations No.111/2022) and its connection to SDGs. This research aims to analyze to what extent Islamic philanthropic institutions can achieve SDGs according to Article 3 [b]. This research used a descriptive qualitative with an empirical juridical approach. Primary data was obtained from interviews and documentation, while secondary data came from legal materials. Atltas.ti software version 9.0 was used to analyze the data. The results show planning was carried out by getting involved in the preparation of a national development plan, contributing to national and regional action plans, and reducing SDG programs in the institution's strategic plan. The implementation, however, only focuses on blended financing schemes and initiates a ‘program follows money’ approach to aligning all programs with SDGs. In terms of monitoring and evaluation, these aspects are still constrained by filling in the reporting matrix, which needs converting. The contribution of this research is to contextualize the role of Islamic philanthropic institutions towards SDGs by providing policy recommendations for the government, such as enhancing the role of philanthropic institutions, developing blended financing schemes, legal reforms, and multisector collaboration. Lembaga filantropi Islam merupakan bagian dari lembaga yang terlibat dalam mewujudkan SDGs di Indonesia dan telah diatur melalui Peraturan Presiden No.111 Tahun 2022. Tujuan penelitian untuk melihat sejauhmana lembaga filantropi Islam dalam mencapai SDGs ditinjau dari sisi regulasi. Jenis penelitian ini adalah deskriptif kualitatif dengan pendekatan yuridis empiris. Data primer diperoleh dari wawancara dan dokumentasi, sedangkan data sekunder berasal dari bahan hukum (perundang-undangan). Seftware Atltas.ti versi 9.0 digunakan sebagai tools untuk mengananalisis data. Hasil penelitian menunjukkan bahwa bentuk perencanaan dilakukan dengan turut terlibat dalam penyusunan rencana pembangunan nasional, pengisian rencana aksi nasional dan daerah, serta menurunkan program SDGs dalam rencana strategis lembaga, dari segi pelaksanaan hanya berfokus pada skema blended finance serta diperlukan inisasi “programme follows money” untuk meng in-line kan seluruh program dengan SDGs, dari segi pemantauan dan evaluasi masih terkendala dengan pengisian matriks pelaporan yang dinilai perlu dikonversi. Penelitian ini berkontribusi dalam wujud konteksualisasi peran lembaga filantropi Islam terhadap pencapaian SDGs sekaligus memberikan rekomendasi kebijakan yang ditujukan kepada pemerintah seperti peningkatan peran lembaga filantropi, pengembangan skema blended finance, pembaharuan hukum dan kolaborasi multi-sektor.